Trade-offs in male display activity with lek size - Cestari, César [UNESP]; Loiselle, Bette A.; Pizo, Marco Aurélio [UNESP] (Public Library of Science (PLoS), 2016)
In lek mating systems, males aggregate and defend arenas where they display for females; females select and mate with a male and then solely raise their offspring. Generally, female visits and copulations increase and reproductive variance in male mating success declines with lek size. Here we investigate how male display effort changes across a gradient in lek size. We expect male display effort, an energetically expensive activity, will increase with lek size and male rank due to changes in breeding opportunities and competition among males. We test the interaction of male rank and lek size on display effort using the white-bearded manakin, Manacus manacus (Aves: Pipridae), a well-studied species with a wide geographic distribution in the new world tropics. We used mini-video recorders to simultaneously capture female visits and display behaviors of 41 males distributed over 10 leks. We found that overall display effort increased disproportionately with lek size due to males of both high and low ranks increasing their display effort at larger leks. Our results suggest that increased breeding opportunities and intrasexual competition at larger leks result in males of different ranks investing similarly in increased display effort in order to attract females.